Takaful: Pros, Cons, and Sentiment Analysis - Siti Fatimah Azzahro (Islamic Social Finance, 2022)
This study aims to determine sentiment towards Islamic insurance in the last 16 years, from 2006 to 2022. The method used is descriptive statistical analysis combined with meta-analysis and sentiment from secondary data in metadata from 100 journals taken from Dimension, then processed using Microsoft Excel 2016 and SentiStrength software. The results of the sentiment analysis show that expert opinions on the development of Islamic insurance vary, with positive sentiments of 37%, negative sentiments of 34%, and neutral sentiments of 29%. Based on the results of the study, it was found that there had been researched on the topic of Islamic insurance in the scientific literature. From the results of this study, it can be seen that there are differences of opinion among some scholars regarding Islamic insurance with the results of the impact of Islamic insurance itself. So, there is a need for cooperation between scholars and Islamic insurance experts to determine the law of Islamic insurance itself. This is complemented by the dissemination of literacy regarding Islamic insurance and its impact on individuals and the country, to increase public awareness of the importance of choosing Islamic insurance by Islamic law to avoid sins and loss of property.